Analysis of the Librarian Certification System in Korea and Measures for Improvement - Kim, Sinyoung; Yoon, Hee-Yoon (International Journal of Knowledge Content Development & Technology, 2021)
Half a century has passed since the academic field of library and information science, which was born at the end of the 19th Century in the Western world, was introduced to Korea. Despite years of quantitative growth and qualitative maturation, the field has been facing the inconvenient truths of discrepancies in education levels arising from varying education providers, and weakened public confidence in librarian certification. Based on analysis of librarian training and education programs and the certification system, this research seeks to point out the limitations of the national librarian certification system, which is losing public confidence, and present a model for improvement. Library and information science education has expanded from universities to librarian training centers and lifelong education centers, and the librarian certification system has emerged as a target of reform. This research presents measures to improve the librarian certification system to government bodies and the Committee on Library and Information Policy with the purpose of providing grounds for policy enforcement.